Predictors of advance directives among nursing home residents with dementia. (29th August 2017) - Huang, Hsiu-Li; Shyu, Yea-Ing Lotus; Weng, Li-Chueh; Chen, Kang-Hua; Hsu, Wen-Chuin
ABSTRACT: Background: Advance directives are important for nursing home residents with dementia; for those with advanced dementia, surrogates determine medical decisions. However, in Taiwan, little is known about what influences the completion of these advance directives. The purpose of this study was to identify factors, which influence the presence of advance directives for nursing home residents with dementia in Taiwan. Method: Our cross-sectional study analyzed a convenience sample of 143 nursing home dyads comprised of residents with dementia and family surrogates. Documentation of residents' advance directives, physical and cognitive status was obtained from medical charts. Surrogates completed the stress of end-of-life care decision scale and a questionnaire regarding their demographic characteristics. Nursing home characteristics were obtained from each chief administrator. Results: Less than half of the nursing home residents (39.2%) had advance directives and most (96.4%) had been completed by family surrogates. The following were predictors of an advance directive: surrogates had previously signed a do-not-resuscitate as a proxy and had been informed of advance directives by a healthcare provider; nursing homes had policies for advance directives and a religious affiliation. Conclusions: Advance directives were uncommon for nursing home residents with dementia. Presence of an advance directive was associated with surrogate characteristics and the nursing home facilities; there was no association with characteristics of the nursing home resident. Our findings emphasize the need to develop policies and strategies, which ensure that all residents of nursing homes and their surrogates are aware of their right to an advance directive.